2019
DOI: 10.1016/j.jses.2018.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of clinically evident isolated axillary nerve injury in 869 primary anatomic and reverse total shoulder arthroplasties without routine identification of the axillary nerve

Abstract: Background It has been suggested that, during primary shoulder arthroplasty, surgeons should identify the axillary nerve through direct visualization, palpation, or the “tug test” to prevent iatrogenic nerve injury. Our goal was to document the rate of isolated axillary nerve injury (IANI) in patients who had undergone primary anatomic total shoulder arthroplasty (TSA) or reverse total shoulder arthroplasty (RTSA) without routine identification of the axillary nerve. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 35 publications
(84 reference statements)
0
12
0
Order By: Relevance
“…The occurrence of nerve complications following rTSA, relates to direct nerve damage, indirect traction, compression secondary to retractors use and post-operative hematoma formation [14]. Isolated axillary nerve stupor [15]. as well as persisting residual dysesthesia in the territory innervated by the median nerve, produced by an injury of the upper sensitive trunk have been described [16].…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of nerve complications following rTSA, relates to direct nerve damage, indirect traction, compression secondary to retractors use and post-operative hematoma formation [14]. Isolated axillary nerve stupor [15]. as well as persisting residual dysesthesia in the territory innervated by the median nerve, produced by an injury of the upper sensitive trunk have been described [16].…”
Section: Discussionmentioning
confidence: 99%
“…9,11,12 LiBrizzi et al showed that the incidence of axillary nerve injury was 0.3% for TSA and 0.9% after rTSA in their study of 869 primary shoulder arthroplasty cases. 20 Similarly, Ball reported a nerve complication rate of 20% for TSA and 22.9% for rTSA, with median nerve and musculocutaneous nerve being most commonly involved. 13 This increased risk of nerve injury is thought to be due to the lengthening of the arm that generally occurs during rTSA that is not present with TSA.…”
Section: Anatomic Vs Reverse Total Shoulder Arthroplastymentioning
confidence: 93%
“…In a retrospective study of 869 TSA and rTSA cases by LiBrizzi et al, one hundred percent of the patients with axillary nerve palsydregardless of whether they had partial or complete sensorimotor deficitsdexperienced complete neurologic recovery by nine months postoperatively. 20 Similarly, Lopiz et al found that most of the axillary nerve lesions due to acute injury during shoulder replacement were transient and had no functional impact at final follow-up, with complete recovery seen on EMG at 6 months postoperatively. 26 6.…”
Section: Prognosismentioning
confidence: 94%
See 1 more Smart Citation
“…(3) Nerve injury is very rare in shoulder arthroplasty. However, in shoulders with stiffness, the risk of nerve injury could increase as excessive soft tissue traction or soft tissue release often is required [51][52][53]. (4) It often is difficult to repair the rotator cuff after implantation.…”
Section: Stiffnessmentioning
confidence: 99%